Incorporating bioaccessibility into health risk assessment of heavy metals in particulate matter originated from different sources of atmospheric pollution. (November 2019) - Liu, Xinlei; Ouyang, Wanyue; Shu, Yiling; Tian, Yingze; Feng, Yinchang; Zhang, Tong; Chen, Wei
Abstract: Rapid industrialization and urbanization have resulted in widespread pollution of airborne particulate matter (PM) containing various heavy metals with adverse human-health effects. Health risk assessment of PM calls for accurate evaluation of the bioaccessibility, instead of the total content, of heavy metals in PM. Here, we demonstrated that the leachable fraction of particle-bound As, Pb, Cr, Mn, Cd, Cu, Ni and Zn in lung fluid within the typical retention duration of particles in human lungs varied drastically among particles originated from different air pollution sources, including coal combustion, biomass combustion, fugitive dust, road dust, construction dust, cement and soil. Moreover, bioaccessibility of heavy metals, particularly in biomass combustion, cement and soil particles, was strongly dependent on pollution sources, and the particulate Cu, Ni, Pb and Cd appeared to be the primary indicators of the source dependence of heavy metal bioaccessibility. Using total rather than bioaccessible concentrations of particle-bound heavy metals not only led to overestimation of the health risk of source particles, but more importantly, inaccurate identification of the high-risk pollution sources and the priority metal pollutants in the source particles. When considering bioaccessibility of particle-bound heavy metals examined in this study, coal combustion products exhibited the highest carcinogenic and noncarcinogenic risks among all source particles, whereas cement particles would be the source with highest risk based on total metal content. As and Mn appeared to be the main drivers for the noncarcinogenic risks of source particles, while As, Ni and Cr were the major contributors to the carcinogenic risks of source particles, significantly different from those based on total contents. This research underlines the importance of incorporating bioaccessibility into health risk indexes of frequently occurring particle-bound heavy metals from specific air pollution sources, which will facilitate risk-based assessment of source contribution and hence effective source regulation of airborne PM. Graphical abstract: Image 1 Highlights: Bioaccessibility of heavy metals in particulate matter depends on pollution sources. Cu, Ni, Pb and Cd determine the source dependence of heavy metal bioaccessibility. High-risk pollution sources are misidentified using total particulate metal content. Priority metal pollutants are misidentified if not consider metal bioaccessibility. Abstract : Capsule: Understanding bioaccessibility of heavy metals in source particles enables accurate identification of high-risk atmospheric pollution sources and priority metal pollutants.